2016
DOI: 10.1371/journal.pone.0157011
|View full text |Cite
|
Sign up to set email alerts
|

Epibiotic Diatoms Are Universally Present on All Sea Turtle Species

Abstract: The macro-epibiotic communities of sea turtles have been subject to growing interest in recent years, yet their micro-epibiotic counterparts are almost entirely unknown. Here, we provide the first evidence that diatoms are epibionts for all seven extant species of sea turtle. Using Scanning Electron Microscopy, we inspected superficial carapace or skin samples from a single representative of each turtle species. We distinguished 18 diatom taxa from these seven individuals, with each sea turtle species hosting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 18 publications
4
49
0
1
Order By: Relevance
“…Another method suggestively having great potential for studying turtle behavior is to study the epibiota on shell turtles. Most of these studies have focused on macro-epibiota but, since the 70s (e.g., [ 21 – 25 ]), micro-epibiota has also received attention and is now the subject of growing interest given the diversity of organisms that live on(e.g., [ 26 – 28 ]). Among the micro-epibiotic organisms, diatoms (Bacillariophyta) receive the most attention because of their diversity and density on turtle shells [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another method suggestively having great potential for studying turtle behavior is to study the epibiota on shell turtles. Most of these studies have focused on macro-epibiota but, since the 70s (e.g., [ 21 – 25 ]), micro-epibiota has also received attention and is now the subject of growing interest given the diversity of organisms that live on(e.g., [ 26 – 28 ]). Among the micro-epibiotic organisms, diatoms (Bacillariophyta) receive the most attention because of their diversity and density on turtle shells [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…from a leatherback turtle in Robinson et al (2016, fig. 2-D), with an internal narrow transapical structure with lateral triangular wing-shaped expansions, and valvocopulae showing apices with a double row of puncta, may be similar to our new taxon.…”
Section: Taxonomic Notesmentioning
confidence: 99%
“…As reported by Wetzel et al (2012), bRaDy (2010) also found an unidentified Epiphalaina or Tursiocola species on several species of marine turtles from the Gulf of Mexico. Recently, Robinson et al (2016) Scrapings from several juvenile Chelonia mydas linnaeus (green turtle) from the Lesser Antilles (Eastern Caribbean) and adults from French Guiana allowed for the description of two additional species that can be assigned to Tursiocola due to their characteristic internal structure. Differences with the eight previously described Tursiocola species are discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…minor se ha aislado desde aguas superficiales de la Antártida (Cefarelli et al, 2016). Especies como Achnanthes sp., se aislaron desde biopelículas del caparazón de tortugas marinas (Robinson et al, 2016). Por otro lado, estudios de Suresh et al, (2016) discuten que Achnanthes sp., es una microalga que induce el asentamiento de macroorganismos, al observar que su presencia en sustrato indujo el asentamiento del poliqueto Hydroides elegans.…”
Section: Tetraselmis Marina) (Tabla 1) En Otros Trabajos Bacillariounclassified